Primera cita ibérica de Brachypalpus valgus ( Panzer , 1798 ) y Chrysotoxum parmense Rondani , 1845 ( Diptera : Syrphidae ): caracterización polínica de su dieta * (Boln. Asoc. esp. Ent, 1995)
The first Iberian specimens of the genus Brachypalpus and species Chrysotoxum parmense ha ve been caught in the Font Roja Natural Park (Alicante, Spain). The presence of these two species and the Psilota anthracina, indícales the importance of this Mediterranean holm oak sheltering threatened species in nearby countries like France and Germany. The pollen Lypes found in the alimentary canal of syrphids, are indicated for the first time.